Study on the mechanical properties and microstructure of fiber reinforced metakaolin-based recycled aggregate concrete. (2nd August 2021) - Liu, Kangning; Wang, Sheliang; Quan, Xiaoyi; Duan, Wei; Nan, Zhao; Wei, Tao; Xu, Fan; Li, Binbin
Highlights: The mechanical properties of RAC with MK and fiber including PF and BF were studied. The pore structure of RAC was analyzed by NMR. The RAC with MK and fiber are studied from macro and micro perspectives. The results that 15% MK and PF cloud enhance the performance of RAC most obviously were showed. Abstract: The paper aimed to study the compound effect of metakaolin (MK) and fiber, including polyvinyl alcohol (PVA) fiber (PF)and basalt fiber (BF) on the recycled aggregate concrete (RAC). Eighteen kinds of RAC were prepared and divided into three groups, namely the RAC mixed with MK (RM) group replacing cement rate of 0%, 5%, 10%, 15%, 20% and 25%, the RM-BF group mixed with 1.3% BF (percentage of cementitious material) based on the RM group, and the RM-PF group mixed with 1.3% PF based on the RM group. The mechanical properties such as compressive strength, splitting tensile strength, flexural strength, and bending toughness were studied, and the pore structure was analyzed by nuclear magnetic resonance (NMR). In addition, X-ray diffraction (XRD) and scanning electron microscope (SEM) were used to analyze the crystal composition and micro morphology. The results showed that MK had a positive effect on the improvement of the mechanical properties and the improvement of microstructure of RAC, and this positive effect first increased and then decreased with the increase of MK substitution rate. For the RM-PF group and RM-BF group, the study indicated that the mechanical properties and microstructure of RAC under the combined effect of fiber and MK were further improved. Especially in terms of mechanical properties, the splitting tensile strength and flexural strength enhancement was more significant. The internal pores of RAC with MK substitution rate of 15% and fibers were significantly reduced, and a large amount of calcium silicate hydrate (C-S-H) gel was generated inside RAC, which had the best adhesion to the fiber. It was believed that RAC with PF and 15% MK had the most significantly enhanced performance.